2017
DOI: 10.3389/fped.2017.00182
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in White Matter Tract Reconstruction with Constrained Spherical Deconvolution and Track Density Mapping in Low Angular Resolution Data: A Pediatric Study and Literature Review

Abstract: IntroductionDiffusion-weighted magnetic resonance imaging (DW-MRI) allows noninvasive investigation of brain structure in vivo. Diffusion tensor imaging (DTI) is a frequently used application of DW-MRI that assumes a single main diffusion direction per voxel, and is therefore not well suited for reconstructing crossing fiber tracts. Among the solutions developed to overcome this problem, constrained spherical deconvolution with probabilistic tractography (CSD-PT) has provided superior quality results in clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…In our study, track density images of WM tracts showed a good performance in distinguishing PSP-RS patients from PD considering a whole brain voxel-based classification analysis. Of note, this study provide further evidence that CSD and TDI can be successfully applied using routine clinical MR protocols with low angular resolution and low b-value (Toselli et al, 2017). This finding is not surprising since the SCP represents probably the tracts that showed the most significant alteration in diffusion properties in PSP-RS patients compared with PD patients and controls.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In our study, track density images of WM tracts showed a good performance in distinguishing PSP-RS patients from PD considering a whole brain voxel-based classification analysis. Of note, this study provide further evidence that CSD and TDI can be successfully applied using routine clinical MR protocols with low angular resolution and low b-value (Toselli et al, 2017). This finding is not surprising since the SCP represents probably the tracts that showed the most significant alteration in diffusion properties in PSP-RS patients compared with PD patients and controls.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, the use of the CSD provides reliable fiber orientation estimations, even in voxels comprised of multiple fiber populations, generating more robust tracts reconstruction (Calamuneri et al, 2018). Of note, this study provide further evidence that CSD and TDI can be successfully applied using routine clinical MR protocols with low angular resolution and low b-value (Toselli et al, 2017). This finding, together with the possibility to implement the TDI procedure in a fully automatic way, suggests that TDI approach may help the clinicians to better understand microstructural WM involvement in several pathologic conditions.…”
Section: Discussionmentioning
confidence: 62%
“…With less diffusion sensitization, as used in this study (b = 1000 s/mm 2 ), this metric is also sensitive to extra-axonal diffusion, and therefore may also reflect axonal hindrance of extra-cellular diffusion and other microstructural factors. Nevertheless, our results, as well as those of Toselli et al (2017), demonstrate that fixelbased approaches have advantages over DTI methods when analyzing single shell data like those collected here. Furthermore, our ability to observe the results reported here using data collected in 32 gradient directions demonstrates that the results are quite robust and suggest the promise of applying this method to existing single-shell lower b-value data.…”
Section: Limitations and Future Directionssupporting
confidence: 58%
“…In addition, we used constrained spherical deconvolution-based tractography in the global analyses, though its acquisition was suboptimal because the diffusion-weighting and the number of gradient orientations were relatively low. 50,51 However, fiber crossings are present in most white matter 36 and can be reliably identified with constrained spherical deconvolution. [32][33][34][35] Moreover, TBSS has limitations, for example, concerning the parameters selected by the user-that is, sensitivity, anatomic specificity, and restriction to only a part of the white matter voxels.…”
Section: Discussionmentioning
confidence: 99%